PENGARUH MODAL INTELEKTUAL, UKURAN PERUSAHAAN DAN STRUKTUR MODAL TERHADAP NILAI PERUSAHAAN DI PERUSAHAAN PERTAMBANGAN - Juraidah, Juraidah; Hermuningsih, Sri; Wiyono, Gendro (Jurnal Pendidikan Ekonomi (JURKAMI), 2024)
Corporate Value is the condition or condition of a company that has been achieved during the operating process of public appreciation of the company. Increased corporate value is an achievement that reflects improved welfare for shareholders. The aim of this research is to identify and analyze the influence of Intellectual Capital (VAIC), Company Size (Ln Size), Capital Structure (DER) on the Company Value projected with Price Book Value (PBV) with Profitability (ROE) as an intervening variable on mining companies listed in the BEI period 2018-2020. This research uses a type of quantitative research with sampling using purposive samplings. Based on the defined criteria obtained 34 samples of companies with a total of 102 data and data analysis using SmartPLS Software 3.2.9. The results of the research showed that intellectual capital had a significant positive impact on the company's value, the size of the company had a substantial negative impact on its value, capital structure had a non-substantial positive influence on the corporate value, profitability had an insignificant negative effect on the value of the enterprise. Results of variable mediation show that profitability cannot mediate the size of the corporate intellectual capital nor the capital structure of the company's value.